REKONTRUKSI MAKNA Al-DU’A DALAM Al-QUR’AN: EKSPLORASI SEMANTIK ATAS PARADIGMA HERMENEUTIKA TOSHIHIKOIZUTSU - Muhammad Raihan Syahid; Herlina; Julfathra Bayyinahdy; Indah Ramadhani Priyono; Andi Rosa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study aims to reconstruct Toshihiko Izutsu’s hermeneutical paradigm through a semantic approach to understanding the meaning of du‘ā (prayer) in the Qur’an. The main problem addressed concerns the limitation of previous studies that described Izutsu’s semantic theory without deeply integrating it into the theological and experiential dimensions of Qur’anic meaning. Employing a qualitative-hermeneutical method, this research analyzes the semantic field of du‘ā in relation to other key Qur’anic concepts such as ‘ibādah (worship) and istijābah (divine response). Data were collected through a textual study of the Qur’an and Izutsu’s major works, including God and Man in the Qur’an (1964) and Ethico-Religious Concepts in the Qur’an (1966). The findings reveal that du‘ā, in Izutsu’s framework, is both a linguistic and existential phenomenon representing a reciprocal dialogue between humans and the Divine. When the initial spiritual tension of prayer becomes stabilized and deeply rooted, du‘ā transforms into ‘ibādah—a continuous mode of worship and divine consciousness. This study contributes to the development of a modern Qur’anic exegesis methodology called Qur’anic Semantic Hermeneutics, which integrates linguistic, theological, and experiential dimensions into a coherent interpretative framework.